Numerical modeling in micromechanics via particle methods - 2004 : proceedings of the 2nd International PFC Symposium, 28-29 October 2004, Kyoto, Japan /: proceedings of the 2nd International PFC Symposium, 28-29 October 2004, Kyoto, Japan. (©2003) - Unknown
No abstract available